PENGARUH TAX AVOIDANCE, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Tatap Maduma; Eduard Ary Binsar Naibaho (ITB AAS INDONESIA, 2022)
THE INFLUENCE OF TAX AVOIDANCE, LEVERAGE, AND PROFITABILITY ON COMPANY VALUE WITH DIVIDEND POLICY AS MODERATING VARIABLES Corporate value is the main goal of every company. This research examines the relationship of tax avoidance, leverage, and profitability to firm value and uses dividend policy as a moderating variable. Tax avoidance is measured using the Cash Effective Tax Rate, leverage is measured using the Debt to Equity Ratio, profitability is measured using Return On Assets, firm value is measured using Tobins q and dividend policy uses the Dividend Payout Ratio indicator. The observation data in this research is from 600 datas of industrial sector companies consisting of capital goods, commercial and professional services, and transportation companies in Southeast Asia, namely Indonesia, Malaysia, Singapore, Thailand, Vietnam and the Philippines from 2015–2020. It uses secondary data from S&P Capital IQ and the company's financial statements. The results of this research indicate that tax avoidance has a positive direction but has no significant effect on firm value, leverage has a negative direction and has a significant effect on firm value, profitability has a positive direction but has no significant effect on firm value, dividend policy as a moderating variable weakens the positive relationship between tax avoidance with firm value, dividend policy as a moderating variable weakens the negative relationship between leverage and firm value, and dividend policy as a moderating variable weakens the positive relationship between capital structure and firm value. Keywords: dividend policy; firm value; leverage; profitability; tax avoidance